Inherent difficulties in understanding History: Proposals to improve comprehension through Easy Reading - Avilés Márquez, Desireé del Mar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The reading comprehension of people with disabilities is a scarcely studied issue and this line of research has not gone in depth into the specific comprehension of specialised texts yet. Consequently, despite the existence of certain procedures to facilitate comprehension, such as easy reading, the difficulties presented by certain texts for people with intellectual disabilities have not been analysed. An example of this are texts on History. This article aims to identify the main comprehension problems surrounding these texts and to formulate possible solutions to facilitate their comprehension.